Strategi Portal Media Berita Online Beritajatim.com Dalam Memperluas Audiens - Pelangi Nerisa Arfina; Windri Saifudin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
The high growth of internet usage has resulted in a shift in the way people access and consume news. This condition encourages competition between online media in capturing the attention and tastes of the audience. This study aims to analyze Beritajatim.com's strategy in expanding its audience reach amidst the dynamics of the digital media industry. The method used is descriptive qualitative with a SWOT and STPD analysis approach to identify internal and external factors that influence Beritajatim.com's position as a news portal. Data analysis techniques through interviews, observation and documentation. The results of the study revealed that audience expansion is an important strategic step for Beritajatim.com, due to the high level of competition, changes in reader tastes, audience fragmentation, and declining revenue. This encourages Beritajatim.com to implement a media convergence strategy as an adaptive step. This strategy is realized through podcast production, content variety, and content distribution across digital platforms to reach a wider audience.